COMPARISON OF THE PRIMARY AND SECONDARY HUMORAL IMMUNE RESPONSE TO VACCINATION BY “PRIORIX” - A. P. Toptygina (Sankt-Peterburg : NIIÈM imeni Pastera, 2014)
Abstract. Twenty healthy children were vaccinated, and then in a 5 years they were revaccinated with Priorix (measles, mumps, rubella vaccine), according to the national immunization calendar. The aim of the study was to observe and compare the shaping and maintenance of immunological memory. Specific IgM, IgA, IgG antibodies in serum, and their subclasses as well as antibodies avidity were tested by ELISA. It was demonstrated that IgM, IgG, and IgA antibodies shaped primary immune response to Priorix. Booster-effect was found in IgG and IgA antibodies in response to revaccination. Low avidity of antibodies in primary immune response changed to the high avidity (60–70%) antibodies of memory response to measles and rubella, and remained low for antimumps antibodies. IgG3 subclass was predominant, and IgG1 and IgG4 subclasses were involved in primary immune response. At the stage of immunological memory IgG1 was predominanted and IgG3 and IgG4 became minor.